Pengaruh Model Pembelajaran Scramble Berbantuan Media Peta Terhadap Minat Belajar IPS Siswa Kelas IV - Ramadania, Ajeng Nurastuti; Idris, Muhammad; Ramadhani, Efran (Indonesian Research Journal on Education, 2022)
This research was motivated by the low interest in learning IPS students of class IV. The purposeof this study is to find out the influence of the map media-assisted scramble learning model on thelearning interests of fourth grade students. The study used experimental quantitative methods and one-group-pretest-posttes design research types. Sampling using random sampling methods. Data collection techniques in this study used the Guttman scale in the form of questionnaires, interviews and documentation. The average on pretest results 17 with a percentage of 61% belongs to the "medium" category, the average on posttest results 23 with a percentage of 82% belongs to the "high" category and the hypothesis test using the Paired Sample t-Test test which shows that the sig value of 2-tailed = 0.000 < 0.05. This proves that the scramble learning model assisted by map media can affect the interests of ips learning of fourth grade students. Then the map mediaassisted scramble learning model can be a solution in increasing students' learning interest in IPS subjects.